Modeling Media Exposure, Appearance-Related Social Comaparison, Thin-Ideal Internalization, Body Image Disturbance And Academic Achievement Of Female University Students - REHMAN, ASAD UR; NAWAL, AYESHA; SARWAR, DR. MUHAMMAD HASEEB; MEHMOOD, HAMID; MAJID, BILAL (The journal of contemporary issues in business and government, 2021)
There is extensive research where social, economic and interpersonal factors influence was investigated in the relationship of academic achievement. However, the studies where social pressure induces via media exposure on students’ academic achievement are scant. Rare studies investigate the social-cultural, socio-psychological, media and marketing constructs that influence academic achievement. This study investigates the sequential mediating effect of appearance-related social comparison, thin-ideal internalization, and body image disturbance in the relationship between media exposure and female university students’ academic achievement in Punjab, Pakistan. Multistage cluster random sampling technique was used for data collection for sampling frame. It is necessary to develop a sampling frame because the population was unknown. The study based on the cross-sectional survey was conducted with 1322 female students across Punjab to develop the sampling frame. Out of 1322 for the final sample, 504 questionnaires were randomly selected using the SPSS random value selection option. However, 20 questionnaires were removed from the sample because of missing values and outliers and a total of 484 survey questionnaires were used for data analysis. Two-stage structural equation modeling is used to measure the causal relationship among constructs. In the first stage, constructs validity and reliability were measured with confirmatory factor analysis. In the second stage, the structural model measures the causal relationship. All the direct hypotheses are statistically significant. Whereas appearance-related social comparison and thin-ideal internalization fully mediate the relationship between media exposure and body image disturbance. Moreover, body image disturbance partially mediates the relationship between appearance-related social comparison and academic achievement and thin-ideal internalization and academic achievement. Findings revealed that greater exposure to media disturbs body image and eventually, female students affect their academic performance.